Influence of Work Environment and Work Discipline towards Productivity at PT. Samudera Luas Paramacitra Cirebon - Darmawan, Resita; Kartono, Kartono; Suzana, Anna (Jurnal Ekuisci, 2024)
Employees are valuable assets that cannot be replaced by anything. Achieving the goals depends on how employees can develop their abilities, knowledge, skills, and attitudes. Apart from human resources, work productivity is one of the benchmarks for achieving company goals. This study aims to obtain empirical evidence of the effect of the work environment and work discipline on productivity. The population in this study were all employees of PT. Samudera Luas Paramacitra Cirebon. The data used in this research is primary data. This type of research uses basic research. The sampling method used is the Slovin method, resulting in 66 samples. Data analysis and hypothesis testing in this study used multiple regression analysis with the help of the SPSS 26 program. The results showed that work environment and discipline variables partially and simultaneously affected productivity.